Congruent responses to weather variability in high arctic herbivores - Stien, Audun (The Royal Society, 2012)
Assessing the role of weather in the dynamics of wildlife populations is a pressing task in the face of rapid environmental change. Rodents and ruminants are abundant herbivore species in most Arctic ecosystems, many of which are experiencing particularly rapid climate change. Their different life-history characteristics, with the exception of their trophic position, suggest that they should show different responses to environmental variation. Here we show that the only mammalian herbivores on the Arctic islands of Svalbard, reindeer (Rangifer tarandus) and sibling voles (Microtus levis), exhibit strong synchrony in population parameters. This synchrony is due to rain-on-snow events that cause ground ice and demonstrates that climate impacts can be similarly integrated and expressed in species with highly contrasting life histories. The finding suggests that responses of wildlife populations to climate variability and change might be more consistent in Polar regions than elsewhere owing to the strength of the climate impact and the simplicity of the ecosystem.